Effects of Mild Cold Shock (25°C) Followed by Warming Up at 37°C on the Cellular Stress Response - Neutelings, Thibaut; Lambert, Charles A.; Nusgens, Betty V.; Colige, Alain C. (PLOS ONE, 2013)
Temperature variations in cells, tissues and organs may occur in a number of circumstances. We report here that reducing temperature of cells in culture to 25°C for 5 days followed by a rewarming to 37°C affects cell biology and induces a cellular stress response. Cell proliferation was almost arrested during mild hypothermia and not restored upon returning to 37°C. The expression of cold shock genes, CIRBP and RBM3, was increased at 25°C and returned to basal level upon rewarming while that of heat shock protein HSP70 was inversely regulated. An activation of pro-apoptotic pathways was evidenced by FACS analysis and increased Bax/Bcl2 and BclXS/L ratios. Concomitant increased expression of the autophagosome-associated protein LC3II and AKT phosphorylation suggested a simultaneous activation of autophagy and pro-survival pathways. However, a large proportion of cells were dying 24 hours after rewarming. The occurrence of DNA damage was evidenced by the increased phosphorylation of p53 and H2AX, a hallmark of DNA breaks. The latter process, as well as apoptosis, was strongly reduced by the radical oxygen species (ROS) scavenger, N-acetylcysteine, indicating a causal relationship between ROS, DNA damage and cell death during mild cold shock and rewarming. These data bring new insights into the potential deleterious effects of mild hypothermia and rewarming used in various research and therapeutical fields.